37LRP induces invasion in hypoxic lung adenocarcinoma cancer cells A549 through the JNK/ERK/c-Jun signaling cascade - Yongan Zhou; Yafang Wang; Zhengwei Zhao; Yanxia Wang; Ning Zhang; Helong Zhang; Lili Liu (Tumor Biology, 2017)
We previously reported that 37-kDa laminin receptor precursor involved in metastasis of lung adenocarcinoma cancer cells. In this study, we further revealed that hypoxia induced 37-kDa laminin receptor precursor expression and activation of extracellular signal–regulated protein kinase, c-Jun N-terminal kinase, and p38 mitogen-activated protein kinase in lung adenocarcinoma cancer cells. In addition, we further demonstrated that the c-Jun N-terminal kinase inhibitor SP600125 and extracellular signal–regulated protein kinase inhibitor U0126 blocked the c-Jun activity and abolished hypoxia-induced 37-kDa laminin receptor precursor expression and promoter activity in a concentration-dependent manner. However, the p38 mitogen-activated protein kinase inhibitor did not affect 37-kDa laminin receptor precursor expression and c-Jun activity in response to hypoxia. Furthermore, downregulated c-Jun expression by short interfering RNA could also inhibit hypoxia-induced 37-kDa laminin receptor precursor expression and transcriptional activity. The inhibition of 37-kDa laminin receptor precursor expression by SP600125 and U0126 could be rescued by c-Jun overexpression. Studies using luciferase promoter constructs revealed a significant increase in the activity of promoter binding in the cells exposed to hypoxia, which was lost in the cells with mutation of the activator protein 1 binding site. Electrophoresis mobility shift assay and chromatin immunoprecipitation demonstrated a functional activator protein 1 binding site within 37-kDa laminin receptor precursor gene regulatory sequence located at −271 relative to the transcriptional initiation point. Hypoxia-induced invasion of A549 cells was inhibited by the pharmacologic inhibitors of c-Jun N-terminal kinase (SP600125) and extracellular signal–regulated protein kinase (U0126) as well as 37-kDa laminin receptor precursor–specific siRNA or antibody. Our results suggest that hypoxia-elicited c-Jun/activator protein 1 regulates 37-kDa laminin receptor precursor expression, which modulates migration and invasion of lung adenocarcinoma cells.